Knowledge, attitudes and practices of primary schools learners on sanitation and hygiene practices - Shilunga, Anna P. K.; Amukugo, Hans J.; Mitonga, Kabwebwe H. (International Journal Of Community Medicine And Public Health, 2018)
Background: Water, sanitation and hygiene played a significant role in schools by reducing water and sanitation related diseases; subsequently improving the health and learning performance of school-aged children. However, ppeople’s knowledge and attitudes on sanitation and hygiene determine the actual practice towards it. This study aimed at assessing and describing the knowledge, attitudes and practices of primary school learners towards sanitation and hygiene. Methods: A quantitative, descriptive design was used. A questionnaire was used to collect data among 450 learners in 10 selected primary schools in Ohangwena region. The study population was grade five, six and seven primary school learners. A three staged probability sampling method was employed. Statistical analysis was done using the Statistical Package for Social Sciences version 23. Results: The result indicated that younger learners in lower school grades, has poorer knowledge, attitudes and practices towards hygiene and sanitation than older learners irrespective of their gender, school circuits or location. This is a logical conclusion because, as learners become older, they become more aware and take precautions about hygiene and sanitation issues. Conclusions: Younger learners in lower school grades, has poorer knowledge, attitudes and practices towards hygiene and sanitation irrespective of their gender, school circuits or location. The older learners become more aware, and cautious about hygiene and sanitation issues comparing to younger learners. The practice and knowledge of sanitation and hygiene are implicated by the reality of the conditions of the sanitation facilities available to them.